The nature of the progression of drought stress drives differential metabolomic responses in Populus deltoides. (23rd January 2019) - Tschaplinski, Timothy James; Abraham, Paul E; Jawdy, Sara S; Gunter, Lee E; Martin, Madhavi Z; Engle, Nancy L; Yang, Xiaohan; Tuskan, Gerald A
Abstract: Background and Aims: The use of woody crops for Quad-level (approx. 1 × 10 18 J) energy production will require marginal agricultural lands that experience recurrent periods of water stress. Populus species have the capacity to increase dehydration tolerance by lowering osmotic potential via osmotic adjustment. The aim of this study was to investigate how the inherent genetic potential of a Populus clone to respond to drought interacts with the nature of the drought to determine the degree of biochemical response. Methods: A greenhouse drought stress study was conducted on Populus deltoides 'WV94' and the resulting metabolite profiles of leaves were determined by gas chromatography–mass spectrometry following trimethylsilylation for plants subjected to cyclic mild (–0.5 MPa pre-dawn leaf water potential) drought vs. cyclic severe (–1.26 MPa) drought in contrast to well-watered controls (–0.1 MPa) after two or four drought cycles, and in contrast to plants subjected to acute drought, where plants were desiccated for up to 8 d. Key Results: The nature of drought (cyclic vs. acute), frequency of drought (number of cycles) and the severity of drought (mild vs. severe) all dictated the degree of osmotic adjustment and the nature of the organic solutes that accumulated. Whereas cyclic drought induced the largest responses in primary metabolism (soluble sugars, organic acids and amino acids), acute onset of prolonged drought induced the greatest osmotic adjustment and largest responses in secondary metabolism, especially populosides (hydroxycinnamic acid conjugates of salicin). Conclusions: The differential adaptive metabolite responses in cyclic vs. acute drought suggest that stress acclimation occurs via primary metabolism in response to cyclic drought, whereas expanded metabolic plasticity occurs via secondary metabolism following severe, acute drought. The shift in carbon partitioning to aromatic metabolism with the production of a diverse suite of higher order salicylates lowers osmotic potential and increases the probability of post-stress recovery.